Toxicological evaluation of the organic phase resulted from the COSORB process - Simu Georgeta-Maria; Coricovac Dorina; Cseh Liliana; Șoica Codruța; Dehelean Cristina; International Symposium on Analytical and Environmental Problems (21.) (2015) (Szeged) (2015)
In this work, the toxicological assesment of the organic phase resulted from the COSORB process was performed. For this purpose, an animal model was used to evaluate the effects of the organic phase on skin physiological parameters after topical application to SKH-1 hairless mice. The obtained results revealed that the constituents of the organic phase induce skin toxicity by disturbing the physiological skin parameters status, which represents the first signs of skin pathology.